Information technology to reduce the irrational use of Proton Pump inhibitors – Narrative review (Research, Society and Development, 2023)
Introduction: Proton pump inhibitors (PPIs) were clinically introduced in 1989 and proved to be effective for the treatment of a wide range of conditions attributable to gastric acid. Over time, they became victims of their own success, being prescribed in excess, in high doses and for longer periods than indicated. On the other hand, information technology (IT) began to be used to assist the learning process, playing an increasingly important role in medical education. Objective: Since IT is such a versatile method of use within the field of medicine and health education, would this resource be able to reduce, through information and education of doctors and patients, the indiscriminate use of IBPS? Method: We performed a narrative review, using MEDLINE, PubMed, SciELO, LILACS, SCOPUS and Google Scholar databases to extract articles. We searched the literature of recent years, with DeCS/MeSH terms used in the search for “proton pump inhibitor”, “medical education”, “gastroenterology” and “boarding school and residency”, in addition to terms such as “prescription”, “ulcer”, “free open access medical education”, “FOAM”, FOAMed”, “information technology”, “medical apps”, “applications”, “proton pump inhibitors”. Result: After extensive research, articles with different educational tools were found, but only two (PINCER and FORTA-EPI) used IT for a more rational prescription of medications. Conclusion: There was a scarcity of publications relating information technology and gastroenterology, as well as the use of proton pump inhibitors, indicating the need for studies that actually prove that there would be a reduction in prescriptions without indication of IBPS and validation of applications for this purpose. In view of the above, it was possible to conclude that feedback interventions and educational guidelines have the possibility of positively guiding medical conduct in clinical practice. In this way, we propose the development of an application to facilitate this difficult area of intervention.